Electrophoretic Separation of the Soluble Protein of Sclerotinia sclerotiorum, S. trifoliorum and S. Minor - Buddy Dani Kosasih (Institute for Research and Community Services (LPPM) ITB, 1975)
Abstract. Soluble proteins extracted from 3 species of Sclerotinia sclerotiorum, S. trifoliorum and S. minor were separated on polyacrylamide gel electrophoresis. The three species of Sclerotinia could be distinguished by their protein patterns.Ringkasan. Ekstrak protein dari Sclerotinia sclerotiorum, S. trifiliorum dan S. Minor, sebagai jamur penyebab penyakit sayur-sayuran, telah dapat dipisahkan dengan cara